Effects of variable fluid properties and thermophoresis on unsteady forced convective boundary layer flow along a permeable stretching/shrinking wedge with variable Prandtl and Schmidt numbers. (January 2016) - Alam, M.S.; Khatun, M. Asiya; Rahman, M.M.; Vajravelu, K.
Abstract: In this paper, the effects of variable fluid properties and thermophoresis on unsteady forced convective boundary layer flow along a permeable stretching/shrinking wedge are studied numerically. The analysis accounts for temperature dependent viscosity and thermal conductivity. The governing time dependent nonlinear partial differential equations are reduced to a set of nonlinear ordinary differential equations by the similarity transformations. The resulting local similarity equations are solved numerically by Nachtsheim–Swigert shooting iteration technique with sixth order Runge–Kutta integration scheme. Comparison with previously published work is performed and the results are found to be in excellent agreement. Numerical results for the non-dimensional velocity, temperature and concentration profiles as well as the variable Prandtl number and the variable Schmidt number are displayed graphically for several sets of material parameters. The effects of the model parameters on the local skin friction coefficient, the rate of heat and mass transfer, and the thermophoretic particle deposition velocity are also tabulated. The results show that for the flow with variable thermal conductivity, the Prandtl number as well as the Schmidt number varies significantly within the boundary layer. Thus, in any physical model where fluid transport properties are temperature dependent, the Prandtl number and the Schmidt number within the boundary layer should be considered as variables rather than constants. Highlights: Effects of variable fluid properties are investigated on the unsteady convective boundary layer flow. The Prandtl and Schmidt numbers must be treated as variable when fluid properties are temperature dependent. Unsteadiness significantly controls the heat and mass transfer characteristics. Thermophoretic particle depositions are influenced by the concentration ratio and the thermophoretic parameter.